Removal of Cadmium Ions from Water by Synthetic Niobia - Érika S. Melo; Kele T.G. Carvalho; Luiz C.A. Oliveira (Adsorption Science & Technology)
The feasibility of using synthetic niobia, both pure and modified with H 2 O 2 , as adsorbents for the removal of Cd 2+ ions from aqueous solution has been studied. Different adsorption isotherms were obtained using Cd 2+ ion concentrations ranging from 10 mg/ℓ to 500 mg/ℓ. At an initial pH value of 4.5, the Cd 2+ ion adsorption capacity of synthetic niobia at 298 K was estimated as 182 mg/g. The Freundlich adsorption isotherm model gave the better fit to the equilibrium adsorption data for Cd 2+ ions. The thermodynamic parameters for the studied system showed that the adsorption process was spontaneous and endothermic. The results obtained suggest that niobia may be employed as an efficient material for the removal of Cd 2+ ions from aqueous solution.